Chloroplast genome of Calamus tetradactylus revealed rattan phylogeny - Haibo Zhang; Peng Liu; Yi Zhang; Huayu Sun; Yue Wang; Zhimin Gao; Xin Liu (BMC Genomic Data, 2024)
Abstract Background Calamus tetradactylus, a species primarily distributed in Vietnam, Laos, and southern China, is highly valued for its utilization as a small-diameter rattan material. While its physical and mechanical properties have been extensively studied, the genomic characteristics of C. tetradactylus remain largely unexplored. Results To gain a better understanding of its chloroplast genomic features and evolutionary relationships, we conducted sequencing and assembly of the chloroplast genome of C. tetradactylus. The complete chloroplast genome exhibited the typical highly conserved quartile structure, with specific variable regions identified in the single-copy region (like psbF-psbE, π = 0.10327, ndhF-rpl32, π = 0.10195), as well as genes such as trnT-GGU (π = 0.05764) and ycf1 (π = 0.03345) and others. We propose that these regions and genes hold potential as markers for species identification. Furthermore, phylogenetic analysis revealed that C. tetradactylus formed a distinct clade within the phylogenetic tree, alongside other Calamus species, and C. tetradactylus was most closely related to C. walkeri, providing support for the monophyly of the genus. Conclusion The analysis of the chloroplast genome conducted in this study provides valuable insights that can contribute to the improvement of rattan breeding programs and facilitate sustainable development in the future.